Penile prosthesis in severe corporal fibrosis: a history of a difficult case using the double corporotomy incision technique - Buranapitaksanti, Dechapol (Insight Urology, 2022)
Penile prosthesis implantation in corporal fibrosis is a significant surgical challenge even for experienced surgeons. As it is a rare occurrence, a small number of series with limited follow-up have been reported. Multiple surgical approaches to eliminate fibrous tissue and to place an implant have been described. In this report, a 48-year-old man had a history of delayed treatment priapism with no response to any erectile dysfunction treatment. Penile prosthesis was recommended but the surgical approach was difficult and complex. It is widely accepted that implanters have to deal with both a high complication rate and patient expectation. This article introduces a new surgical approach in this challenging case.